2019
DOI: 10.1098/rstb.2019.0028
|View full text |Cite
|
Sign up to set email alerts
|

Distinct colours in the ‘synaesthetic colour palette’

Abstract: In grapheme-colour synaesthesia, particular linguistic elements evoke particular colour sensations. Interestingly, when asked, non-synaesthetes can also associate colours to letters, and previous studies show that specific letter-to-colour associations have similar biases to those of synaesthetes. However, it is an open question whether the colours reported by synaesthetes and non-synaesthetes differ overall : is there a ‘synaesthetic colour palette’? In this study, we visualize the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 60 publications
3
10
0
Order By: Relevance
“…To do so, the CIELab values were converted into Berlin-Kay color categories (Berlin and Kay, 1969) using the online application Colournamer (Mylonas et al, 2010(Mylonas et al, , 2013, a computation model trained by over 3,000 participants, which returns for color inputs the most likely color name in several languages and its Berlin-Kay color category in English. This method of converting 3D color space coordinates into Berlin-Kay color categories has been used in the recent studies assessing typical grapheme-color associations (Root et al, 2017(Root et al, , 2019Rouw and Root, 2019). Upon visual inspection, the algorithm appears less precise for colors close to the grayscale axis (at a saturation below 1).…”
Section: Color Category Analysismentioning
confidence: 99%
“…To do so, the CIELab values were converted into Berlin-Kay color categories (Berlin and Kay, 1969) using the online application Colournamer (Mylonas et al, 2010(Mylonas et al, , 2013, a computation model trained by over 3,000 participants, which returns for color inputs the most likely color name in several languages and its Berlin-Kay color category in English. This method of converting 3D color space coordinates into Berlin-Kay color categories has been used in the recent studies assessing typical grapheme-color associations (Root et al, 2017(Root et al, , 2019Rouw and Root, 2019). Upon visual inspection, the algorithm appears less precise for colors close to the grayscale axis (at a saturation below 1).…”
Section: Color Category Analysismentioning
confidence: 99%
“…Together, these four articles [10][11][12][13] provide a snapshot of how investigations of grapheme-colour (and related forms of ) synaesthesia are being used to address deep-seated questions about cognitive development, language acquisition, and the interplay of genes and environment in our learning processes.…”
Section: Learning In Colourmentioning
confidence: 99%
“…The authors propose a model in which environmental factors evoke associations between graphemes and colours in all people (children and adults; synaesthetes and non-synaesthetes), but that children with a synaesthetic predisposition 'lock in' particular associations during development, yielding the stable associations in adulthood that are hallmarks of the condition [12]. In a related paper, Rouw & Root [13] note that while synaesthetes and non-synaesthetes may show similar biases in the specific letter-colour associations that they report, it has not previously been determined whether the colours themselves differ in their properties. The authors find that, compared with colour associations reported by non-synaesthetes, the colour concurrents of synaesthetes have an over-representation of unmixed hues, with the increased presence of warm (yellow-orange/brown) and achromatic (grey, white and black) colours [13].…”
Section: Learning In Colourmentioning
confidence: 99%
See 2 more Smart Citations